Play-based interventions to support social and communication development in autistic children aged 2–8 years: A scoping review. (June 2021) - Gibson, Jenny L; Pritchard, Emma; de Lemos, Carmen
Background and aims: Play is used by practitioners from across disciplinary backgrounds as a natural and enjoyable context for providing intervention and support in early childhood. In the case of autism interventions, many therapies are based on the association between social play and the development of social skills, language development, and communication skills, as these are often particular areas of challenge for autistic children. However, play is a wide-ranging concept and the extant literature on play-based interventions is large and heterogeneous. This means it is challenging for practitioners and families to navigate the evidence base and make choices about differing intervention strategies. This review aims to provide a comprehensive map of the research on this topic and to develop a conceptual framework to inform clinical decision-making. Methods: An initial stakeholder consultation confirmed the relevance of the topic to practitioners and autistic people. A scoping review methodology (preregistered) was used to identify relevant literature. We systematically searched seven databases to find peer-reviewed primary intervention studies of play-based approaches targeting language, social and communication outcomes for autistic children aged 2-8 years. We then summarised the literature using narrative synthesis and Evidence Gap Maps (EGMs). The literature was summarised according to a range of characteristics, including study design, population characteristics, agent of intervention and outcomes measured, among others. These summaries were then used to develop a framework for some key considerations for practitioners appraising play-based approaches. Results: 388 studies met inclusion criteria. Approximately 21% of studies were RCTs, and over 50% had ≤10 participants. Over 45% of studies reported multiple relevant outcomes, with social play skills being the most common single intervention target. Girls and minority background groups are under-represented. A range of intervention types were identified, and some high-level categorisations are proposed. Main contribution: On the basis of the evidence synthesis we suggest important dimensions for appraisal of play-based interventions, including the role of play within an intervention (as a context, a key developmental mechanism, or a component of a larger approach), the underpinning philosophy (e.g. behaviourist or developmental), and the role of the practitioner (providing parent feedback, 1:1 intervention, group facilitation). Conclusions: The wide range of approaches uncovered by this review is a testament to the wonderful diversity inherent to both play and autism. However, research could usefully focus on consolidating the evidence base for existing approaches, rather than aiming for further diversification. Implications: The conceptual framework proposed in this review can help practitioners appraise the literature and aid their advice to families when making shared intervention decisions.